Decalogue of the Characteristics of Postcolonial Literature: A Proposal of a Taxonomy for Literary Criticism and Comparative Literature Studies - Fernandez-Ruiz, Maria (My University, 2021)
This paper aims to offer a classification proposal of the features that are typically found, to a greater or lesser extent, in postcolonial texts in any language. In spite of the fact that this tax- onomy model is based on previous theoretical definitions of the key concepts related to postco- lonial literature (Edwards 2008, Nayar 2008, and Ramone 2011), it seems to be the first formal classification to be devised. It examines well-established concepts, presents the new notion of plasticity of literary genres and explores the current trends regarding research on intersectional- ity. The decalogue of characteristics of postocolonial literature obtained as a result will facilitate literary criticism and comparative literature studies.
PUBLISHED
Keywords: Postcolonial literature, Taxonomy, Literary theory, Postcolonial criticism, Plasticity